Implementasi Program Tahfidzul Qur'an dalam Meningkatkan Kecerdasan Spiritual Siswi MTs Al-Jihadul Chakim Gondang Mojokerto - Nisa, Lulu' Khoirun; Mufaizah, Mufaizah; Huda, Masrur (YASIN, 2025)
The implementation of tahfidzul Qur'an is very important in developing a generation that excels in religious knowledge. This research examines the tahfidzul Qur'an program at MTs Al-Jihadul Chakim in increasing students' spiritual intelligence. Spiritual intelligence obtained from Tahfidzul Qur'an includes: 1) Foundations of Faith; 2) Discipline and Patience; 3) Wisdom and Wisdom; 4) Calmness and Inner Peace; 5) Empathy and Compassion; 6) Connection with the Creator. This research aims to: 1) Understand the concept of implementing the Tahfidzul Qur'an program at MTs Al-Jihadul Chakim Gondang Mojokerto; 2) Knowing the spiritual intelligence of students at MTs Al-Jihadul Chakim Gondang Mojokerto; 3) Knowing the supporting and inhibiting factors for the Tahfidzul Qur'an program in increasing students' spiritual intelligence at MTs Al-Jihadul Chakim Gondang Mojokerto. This research is a deductive qualitative research that analyzes, observes and describes the research results in depth. Data was collected through interviews, observation and documentation at MTs Al-Jihadul Chakim Gondang Mojokerto with data sources from the head of tahfidz, tahfiz teachers, PAI teachers and students. The research results show that: 1) The tahfidzul Qur'an program is implemented with three contributions: memorizing what has been memorized, repeating previous memorization, and reciting binadzor to prepare for the next memorization; 2) Implementation of the tahfidzul Qur'an program has a positive impact on students' spiritual intelligence such as patience, selfmotivation, emotional control, responsibility, and increased worship; 3) Supporting factors: effective memorization methods, teacher qualifications, student motivation and personal awareness. Inhibiting factor: students' lack of fluency in reciting the Koran, especially new students.